2016
DOI: 10.4269/ajtmh.16-0370
|View full text |Cite
|
Sign up to set email alerts
|

Malarial Infection and Curable Sexually Transmitted and Reproductive Tract Infections Among Pregnant Women in a Rural District of Zambia

Abstract: Abstract. Malarial infection and curable sexually transmitted and reproductive tract infections (STIs/RTIs) are important causes of adverse birth outcomes. Reducing the burden of these infections in pregnancy requires interventions that can be easily integrated into the antenatal care (ANC) package. However, efforts to integrate the control of malarial infection and curable STIs/RTIs in pregnancy have been hampered by a lack of evidence related to their coinfection. Thus, we investigated the prevalence of coin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 49 publications
1
21
0
1
Order By: Relevance
“…The high prevalence of BV (37.3%; 95%CI 33.9-40.9) in this HIV uninfected pregnant population in South Africa is consistent with other sub-Saharan African pregnant populations (Zimbabwe 32.6%, Zambia 48.3%) [20,21] and other South African studies of nonpregnant women at risk for HIV acquisition [22][23][24]. Our study is the first large cohort study of 750 HIV uninfected pregnant women of all ages attending primary health care clinics in a high HIV burden subdistrict of KwaZulu-Natal.…”
Section: Discussionsupporting
confidence: 87%
“…The high prevalence of BV (37.3%; 95%CI 33.9-40.9) in this HIV uninfected pregnant population in South Africa is consistent with other sub-Saharan African pregnant populations (Zimbabwe 32.6%, Zambia 48.3%) [20,21] and other South African studies of nonpregnant women at risk for HIV acquisition [22][23][24]. Our study is the first large cohort study of 750 HIV uninfected pregnant women of all ages attending primary health care clinics in a high HIV burden subdistrict of KwaZulu-Natal.…”
Section: Discussionsupporting
confidence: 87%
“…The prevalence of BV among pregnant women in this region was the highest as cumulative, which gives 38.7% (Table 1), whereas individually, these studies were much lower than that of eastern and western studies. Of the four studies reported from this region, the highest prevalence of BV was reported from Zambia among the rst ANC attendees in Nchelenge District with a prevalence of 48.3% [31]. But, an across-sectional study conducted in South Africa among HIV positive and negative pregnant women shows a low prevalence of BV (17.7%) [32].…”
Section: Southern Africamentioning
confidence: 92%
“…However, few studies from the eastern part of Africa also reported a very low prevalence of BV from studies reported especially from Uganda [9] and Ethiopia [25]. High prevalence of BV was reported not only from the eastern region but also from the western region (highest prevalence's from Nigeria (56.6% and 60%) [10,20] and Cameroon (45.8%) [29]) and southern regions of Africa with the highest prevalence reported from Zambia 48.3% [31].…”
Section: Agementioning
confidence: 96%
See 1 more Smart Citation
“…11 Dihydroartemisininpiperaquine alone-as SST, IST, or IPT-is unlikely to provide similar dual-protection, although this might be inconsequential in Indonesia if co-infection is less common than in Africa. 12 However, pregnant women in Papua New Guinea probably shoulder a dual-burden of infection, 13,14 similar to their African counterparts. 15 Nonetheless, the evidence presented by Ahmed and colleagues is important and shows that IPT with dihydroartemisinin-piperaquine might help to shape a WHO strategy that protects pregnant women in the Asia-Pacific region against P falciparum and P vivax infections.…”
Section: Devising a Strategy For Prevention Of Malaria In Pregnant Womentioning
confidence: 99%